2013
DOI: 10.1051/epjconf/20136018011
|View full text |Cite
|
Sign up to set email alerts
|

Searching for supersymmetry inZ’decays

Abstract: Abstract. I investigate production and decay of heavy neutral gauge bosons Z ′ in GUT-inspired U(1) ′ groups and in the Sequential Standard Model. In particular, decays into supersymmetric particles, such as slepton, chargino and neutralino pairs, as predicted in the MSSM, are accounted for, with a special interest in final states with leptons and missing energy. For a representative point of the parameter space, it is found that the inclusion of supersymmetric decay modes has an impact of 200-300 GeV on the Z… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…[8,9,12] yielded substantial decay rates into supersymmetric particles and was consistent with the present exclusion limits, but did not take into account for the recent discovery of a Higgs-like boson. In this paper, I shall extend the work in [8,9] giving some useful benchmarks for possible Z searches within supersymmetry.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…[8,9,12] yielded substantial decay rates into supersymmetric particles and was consistent with the present exclusion limits, but did not take into account for the recent discovery of a Higgs-like boson. In this paper, I shall extend the work in [8,9] giving some useful benchmarks for possible Z searches within supersymmetry.…”
Section: Introductionsupporting
confidence: 67%
“…Although SM decays are still dominant and the most promising for the searches, the opening of new channels decreases the branching ratios into electron and muon pairs and therefore the mass exclusion limits. Reference [12], using a representative point of the MSSM parameter space as in [8,9], found that the LHC exclusion limits decrease by an amount m Z 150-300 GeV, once accounting for BSM decay modes at √ s = 8 TeV. From the viewpoint of supersymmetry, the lack of evidence of new particles in the LHC runs at 7 and 8 TeV, together with the discovery of a boson with mass m h = 125.7± 0.4 GeV [13] and properties consistent with the Standard Model Higgs boson [14,15], sets some tight constraints on the mass spectra and couplings of possible supersymmetric models.…”
Section: Introductionmentioning
confidence: 99%
“…(3.1) are allowed to vary in the ranges given in Table II, the lower bound on the mass of the Z boson being the minimum value allowed for any choice of the U (1) symmetry (and corresponds to the U (1) η case). This mass has been taken smaller than the one quoted in the 2016 Particle Data Group review [59] in order to allow for significant branching fractions for the Z boson decays into a pair of supersymmetric particles [64]. We have retained scenarios for which the predictions for the observables listed in Table III agree the Higgs sector, namely a theory-experiment agreement for the Higgs boson mass, the gluon and vector boson fusion Higgs boson production cross-sections, and the Higgs signal strengths, have been applied by using HiggsBounds and HiggsSignals.…”
Section: Technical Setupmentioning
confidence: 99%
“…U(1) ′ gauge groups and Z ′ bosons arise in the framework of a rank-6 Grand Unification group E 6 . The Z ′ ψ is associated with U(1) ′ ψ , coming from the breaking of E 6 into SO(10):…”
Section: Theoretical Frameworkmentioning
confidence: 99%